Total synthesis of the natural product EBC-329 - Thombal, Raju S.; Jadhav, Vrushali H. (Organic & Biomolecular Chemistry, 2015)
The first total synthesis of an anti-leukemic diterpene natural product EBC-329 (1) has been accomplished starting from readily available 6,6-dimethyl-3-oxabicyclo[3.1.0] hexane-2,4-dione (7). An efficient and general approach has been reported for the synthesis of EBC-329 in 13 steps with an overall yield of 10%.